Photolysis and TiO2-catalysed degradation of diclofenac in surface and drinking water using circulating batch photoreactors - Devagi, Kanakaraju; Motti, Cherie A.; Glass, Beverley D.; Oelgemöller, Michael (Csiro Publishing, 2014)
The occurrence of diclofenac (DCF) as an emerging pollutant in surface waters and drinking water has been attributed to elevated global consumption and the inability of sewage treatment plants to remove DCF. In this study, DCF spiked drinking water and river water was subjected to photolysis and TiO2 photocatalytic treatments in a circulating laboratory-scale (immersion-well) and a demonstration-scale loop reactor (Laboclean). The operational parameters for the immersion-well reactor were optimised as follows: TiO2 P25 loading, 0.1 g L–1; natural pH, 6.2; initial concentration, 30 mg L–1; water type, distilled water. Complete DCF removal was realised within 15 min under the optimised conditions using the immersion-well reactor. Sunlight-mediated photochemical degradation required a prolonged exposure period of up to 360 min for complete DCF removal. DCF in distilled and drinking water was efficiently degraded in the larger Laboclean reactor. Differences were, however, observed based on their pseudo-first-order rate constants, which implies that the water matrix has an effect on the degradation rate. Six major photoproducts, 2-(8-chloro-9H-carbazol-1-yl)acetic acid, 2-(8-hydroxy-9H-carbazol-1-yl)acetic acid, 2,6-dichloro-N-o-tolylbenzenamine, 2-(phenylamino)benzaldehyde, 1-chloromethyl-9H-carbazole and 1-methyl-9H-carbazole, generated from TiO2 photocatalysis of DCF were identified by liquid chromatography–mass spectrometry (LCMS) and Fourier transform–ion cyclotron resonance–mass spectrometry (FT-ICR-MS). This work has shown that photocatalytic degradation kinetics of DCF are dependent on both the geometry of the photoreactor and the nature of the water matrices.